The dynamics of dissolved inorganic nitrogen species mediated by fresh submarine groundwater discharge and their impact on phytoplankton community structure - Liang, Wenzhao; Liu, Yi; Jiao, Jiu Jimmy; Luo, Xin (The Science of the total environment, 2020)
[Display omitted] •DIN is a key nutrient mediating phytoplankton community, when DIP effects biomass.•Fresh SGD influences the NH4+:NO3– ratio through physical and chemical processes.•Though with high nutrient loading, saline SGD minorly effects NH4+:NO3– ratio. Submarine groundwater discharge (SGD)-driven nutrient inputs have long been speculated to sustain the high frequency of red tide occurrence in Tolo Harbour, Hong Kong, for its larger flux and higher nutrient loadings than river discharge. Based on analysis of high resolution time series biogeochemical and climatological data from 2000 to 2015, fresh SGD-derived dissolved inorganic nitrogen (DIN) is found to be a significant regulator of the annual cycle of phytoplankton community structure in the harbour. In the wet season, fresh SGD supplies nutrients with NH4+:NO3– ratio < 1 to the seawater, meanwhile creates an intensive vertical stratification environment. As a result, diatom which is a NO3– specialist, is prone to be the major group in the harbour. Fresh SGD delivers a same orders of magnitude of DIN as river and precipitation, but it is more important to phytoplankton community structure dynamics because fresh groundwater has smaller NH4+:NO3– ratio that significantly changes the ratio in the harbour. In the dry season, with the decline of fresh SGD and the ease of stratification, vertical mixing uplifts the nutrient (NH4+:NO3– ratio > 1) released from the bottom sediment leading to a NH4+ dominant environment in water column. Dinoflagellate and other groups then become dominant species of phytoplankton in the harbour. Fresh SGD has a major influence on the NH4+:NO3– ratio in the seawater compared to tide-driven SGD, even though the latter contributes a larger proportion SGD. Tide-driven SGD also produces NH4+ and NO3–, but NH4+:NO3– ratio are mainly subject to the beach environment (bare/mangrove beach), which does not change much seasonally, thus dominant DIN species do not change significantly throughout a year. In a conclusion, fresh SGD plays the most important role among all the endmembers in regulating the DIN composition in Tolo Harbour and its fluctuation mediates the phytoplankton community structure.